Beyond choice of entry mode : How and why SMEs change foreign operation modes during internationalization? - Kojola, Antero Elias (My University, 2021)
Due to the continuously increasing competition between companies in a global context, the international operations of firms have become increasingly researched subject among scholars. While the research on the choice of operation modes in foreign markets have already gained vast interest, little is researched about mode changes and especially reasons causing the mode change decisions. Therefore, the purpose of this thesis is to improve the understanding of how and why small and medium sized enterprises change their foreign operation modes. The framework of this thesis is developed by the reviewing literature as well as previous studies on the characteristics of small and medium enterprises, types of foreign operation modes, mode changes and reasons for mode changes. The data for the empirical part was collected through a questionnaire and the final sample consisted of six firms. Accordingly, five dealt with mode increases and one with mode decrease. Empirical findings suggest that managerial attitudes, firm´s performance, firm´s internal environment and external environment all impact the mode change decisions. More specifically, managerial attitudes stimuli dominates both mode directions of mode change decisions, while external environment tends to be the least significant stimuli regarding both direction of mode changes. However, the discussions with the CEOs during the filling of the questionnaire as well as the results from the study highlighted the fact that finding the right partner firm tends to be a significant challenge for international companies, usually resulting as mode increase decision in order to gain more control.
Keywords: internationalisation; small and medium-sized enterprises; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business